A fast vector radiative transfer model for the atmosphere-ocean coupled system. (December 2019) - Ding, Jiachen; Yang, Ping; King, Michael D.; Platnick, Steven; Liu, Xu; Meyer, Kerry G.; Wang, Chenxi
Highlights: A fast vector RTM facilitating polarimetric remote sensing applications. A fast regression-based method to account for inhomogeneous atmospheric absorption. A two-component method for multiple scattering. An efficient computational approach for thermal emission. An ocean module accounting for rough air-sea interface and ocean IOPs. Abstract: To infer atmospheric and oceanic constituent properties from polarimetric observations, an efficient and accurate retrieval algorithm is desirable. In-line radiative transfer calculations are indispensable if a large state vector, including both atmospheric profiles and surface properties, is used to improve retrieval accuracy. However, in-line radiative transfer calculations are usually not computationally efficient for remote sensing applications. Therefore, there is a pressing need to develop an accurate and fast vector radiative transfer model (RTM) to fully utilize spaceborne polarimetric observations. This paper reports on a fast vector RTM, referred to as TAMU-VRTM, in support of polarimetric remote sensing, which is capable of simulating the Stokes vector values observed at the top of the atmosphere and at the surface by fully considering absorption, scattering, and emission in the atmosphere and ocean. Gaseous absorption is parameterized with respect to gas concentration, temperature, and pressure, by using a regression method applicable to an inhomogeneous atmospheric path. An efficient two-component approach combining the small-angle approximation and the adding-doubling method is utilized to solve the vector radiative transfer equation (RTE). The thermal emission component of the RTE solution is obtained by an efficient doubling process. The air-sea interface is treated as a wind-ruffled rough surface in the model to mimic a realistic ocean surface. Several oceanic optical property models are introduced to model ocean inherent optical properties. To demonstrate the applicability of the TAMU-VRTM, simulations are compared with satellite observations, and results from other vector radiative transfer methods including benchmarks.